2005
DOI: 10.1007/s10457-005-0503-z
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Zebu Steers Grazing on Western Tanzania Native Forages Supplemented with Leucaena Leucocephala Leaf Meal

Abstract: Information is lacking on the potential of leguminous fodder trees such as Leucaena leucocephala as a feed resource to supplement the native forages in traditional grazing management systems in the tropics. Two studies were conducted (1) to assess traditional fodder banks' forage nutritive potential on animal production, and (2) to investigate the effect of Leucaena leucocephala leaf meal (LLM) supplementation on growth of steers grazing standing hay basal forages in the dry season. The traditional forages had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 9 publications
3
7
0
Order By: Relevance
“…Fibre fraction defines extent and rate of feed digestibility (Rubanza et al, 2005). The observation that rangeland biomass declined from autumn to winter and CP values were low (3-4%) concurs with literature (Tainton, 1999;Devendra and Sevilla, 2002).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Fibre fraction defines extent and rate of feed digestibility (Rubanza et al, 2005). The observation that rangeland biomass declined from autumn to winter and CP values were low (3-4%) concurs with literature (Tainton, 1999;Devendra and Sevilla, 2002).…”
Section: Discussionsupporting
confidence: 89%
“…The low intake of Acacia species could be ascribed to the presence of condensed tannins. The condensed tannin concentration observed for A. karroo (74 g/kg DM) was above 60 g/kg DM, which confer bitterness and astringency resulting in low palatability and depression of voluntary feed intake (Makkar, 2003;Rubanza et al, 2005). Similar to findings of the present study, Kaitho et al (1997) and Maasdorp et al (1999), reported that intake of Acacia species improves over-time as the animals adapt to the diet.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Multiple purpose trees, such as leucaena (Leucaena leucocephala), have proven to be effective by improving nutrient utilisation, leading to improving nutrient intakes (Majuva-Masafu and Linington 2006), nutrient digestibility and animal performance (Rubanza et al 2005) and lactation (Ghosh et al 2007) and also reduce the use of expensive concentrates (Jetana et al 2011). The farmers who raise buffaloes are not motivated to use this plant.…”
Section: Introductionmentioning
confidence: 99%